Report on Pilot Study on Migration to Accrual Accounting : Forest and Health Departments of State Government of Madhya Pradesh (India) - World Bank (Washington, DC, 2013)
The objective of this study is to identify gaps between the existing cash based accounting system and the accrual based accounting system to assist Government Accounting Standards Advisory Board (GASAB) to address issues related to Property, Plant and Equipment (PPE) and inventories during actual migration to accrual accounting. This study also includes documentation of operational and implementation issues and suggested solutions to latent problems and road blocks if any so as to provide necessary inputs to GASAB for framing appropriate. Guidelines for migration of Government accounts from cash basis to accrual accounting system. The study is noteworthy that not only statement of financial position for the reporting entity has been prepared but it also discloses physical assets and current liabilities. Maintenance of proper records of various classes of assets (constructed, acquired or donated), inventories, receivables and carry over as prescribed in the financial rules and departmental regulations is a starting point for transition to accrual accounting.